A total systems study on APowers Corporation beverage distributor in Marikina City - Castro, Nova Monique; Castro, Regina; De Sagun, Paulyn Angela; Sadava, Erika Pauline
APowers is a distribution of San Miguel, Coca-Cola, and RC products in Marikina. It caters to the demands of sari-sari stores, bars, and restaurants in areas from Marikina, Cubao, Libis, and up to Rizal. Being a beverage distributor, inventory and flow of goods affects the efficiency of its operations. This project aims to improve the operations of the company by focusing on its inventory management. Interviews adn records in sales, ordering, and inventory were used to analyze the current system condition of the company. Given these information, exploratory tools such as the Ishikawa diagram and stream diagnostic chart were utilized to identify the specific pain points of the company. It was found out that 50% of the San Miguel products the company tools that problems can be traced from poor inventory management. From here, alternatives were formulated to alleviate the current conditions of the San Miguel product inventories. After deliberation, the proposed alternative was to install a computerized database system that can monitor the company's inventory levels. The database will allow real-time tracking of the flow of the goods and will also aid the operations supervisor in her decision making with respect to the ordering of the products from supplier through its forecasting feature. A manual simulation was done to test the theoretical effectiveness of the proposed alternative. Results of the simulation showed that with the implementation of the new database, all stockout risks will be reduced to 0% while days in inventory of overstocked products will be reduced as well. In effect, this will increase the company's monthly revenues. While the simulation produced positive results, there are still uncertainties that needs consideration. To conclude the study, uncertainty analyis was done on the proposed system and areas for further studies were also identified.